A new cheilostome bryozoan genus, Abditoporella (Hippoporidridae), from the eastern Pacific - Sosa-Yañez, Armando; Vieira, Leandro M.; Solís-Marín, Francisco A. (Zootaxa, 2015)
Abditoporella dimorpha n. gen. et n. sp. is described from the Pacific coast of Mexico. It was previously misidentified as Odontoporella adpressa (Busk). Abditoporella seems to be morphologically related to Hagiosynodos Bishop & Hayward, 1989 in having a similar orifice and pseudoporous frontal shield, but is distinguished by having dimorphic zooids. A second species, Hippopodinella turrita Osburn, is reassigned to the new genus as Abditoporella turrita n. comb. Abditoporella is included in the Hippoporidridae.